Surgical Reconstruction of Mitral Restenosis Complicated by a Critically Small Left Ventricular Cavity and Giant Left and Right Atriomegaly (Clinical Case) - Volodymyr V. Popov; Oleksandr O. Bolshak; Valery Zh. Boukarim; Olena V. Khoroshkovata; Oleksii M. Gurtovenko; Kateryna V. Pukas (Ukrainian Journal of Cardiovascular Surgery, 2023)
Background. Comprehensive reconstruction of the left and right parts of the heart in giant left atriomegaly, adequate tactics of mitral valve replacement in case of concomitant tricuspid insufficiency and dilation of the right atrium lead to an improvement in the functional state of the myocardium as early as at the hospital stage.Case description. Patient B., a 67-year-old woman, was examined and treated from July 12 to August 2, 2016 at the Department of Surgical Treatment of Acquired Heart Diseases of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine with a diagnosis: stage IV mitral restenosis, condition after closed mitral commissurotomy in 2001, critically small cavity of the left ventricle, giant left atriomegaly, IV degree tricuspid insufficiency, right atriomegaly, high pulmonary hypertension, permanent form of atrial fibrillation for 15 years since 2001, NYHA class IV heart failure, IIB.The patient underwent surgical intervention: mitral valve replacement + W-shaped plastic surgery of the left atrium in combination with dosed resection of left atrium + tricuspid valve plasty with the imposition of a support ring + resection of the right atrium.Conclusion. Given the initial serious condition of the patient with advanced mitral restenosis, critically small left ventricular cavity, giant left atriomegaly of 169.4 × 115.8 mm (according to computed tomography) and high pulmonary hypertension (65 mm Hg), concomitant pathology of the right parts of the heart (tricuspid insufficiency and right atriomegaly), adequate tactics in mitral valve replacement and radical correction of the left atriomegaly lead to an improvement in the functional state of the heart as early as at the hospital stage.